LEGALITY OF CONTRACEPTIVE USE IN CHILDREN AND ADOLESCENTS BASED ON GOVERNMENT REGULATION NO. 28 OF 2024 - Satrio Bagus Tatag Ananto; Wiwik Afifah (Progressive Law Review, 2024)
This study aims to find out how the legality of contraceptive use in children and adolescents is based on Government Regulation No. 28 of 2024. The method used in this study is normative juridical using a statutory approach and a conceptual approach. The focus of the research is on adolescent reproductive health rights and human rights principles, as well as the challenges and implications of such policies. Although it aims to reduce the number of unwanted pregnancies among adolescents, the regulation has raised a variety of controversies, including moral and cultural issues. The results of this study show that the legality of the use of contraceptives for children and adolescents based on Government Regulation No. 28 of 2024 is still limited by strict legal provisions. Although this policy aims to protect the reproductive health of adolescents, restricting access to contraceptives can actually increase the risk of unwanted pregnancies and the spread of sexually transmitted diseases. Therefore, there needs to be a balance between legal regulations, health education, and social values to ensure better protection for adolescent reproductive health in Indonesia.